Giant strain response with low hysteresis in potassium sodium niobate based lead-free ceramics. Issue 12 (15th August 2019) - Yu, Lixiang; Xi, Hao; Yu, Zhenglei; Liu, Yunfei; Lyu, Yinong
Abstract: In this work, the relationships between the composition-driven phase boundary, ferroelectricity and strain properties of the (1- x )(K0.48 Na0.52 )(Nb1- y Sb y )O3 - x Bi0.5 (Na0.82 K0.18 )0.5 ZrO3 (abbreviated as (1- x )KNN1- y S y - x BNKZ) ceramics were investigated. A giant electric field-induced strain of 0.3% ( d 33 ∗ = 750 p.m./V) and a low hysteresis (16.4%) were obtained in the 0.97KNN0.98 S0.02 -0.03BNKZ ceramics. The giant strain is attributed to the enhanced piezoelectricity induced by the appearance of the O-T phase boundary and the electric-field-induced phase transition from the relaxor phase to the ferroelectric phase. Furthermore, the 0.97KNN0.98 S0.02 -0.03BNKZ ceramics exhibit good thermal stability in the temperature range from 25 °C to 150 °C. Hence, this work can promote the practical applications of KNN-based lead-free piezoelectric ceramics in highly sensitive and precise piezoelectric actuators.